Analysis for the results of geomagnetic storms measured by Macau Science Satellite-1 - HaiSheng Ji; Dong Li; HongBo Yao; JianPing Li; YanJie Zhang (Earth and Planetary Physics)
Strong flares and/or coronal mass ejections (CMEs) could bring us disastrous space weather, destroy crucial technology in space, and cause a large-scale blackout during some extreme cases. They frequently cause geomagnetic storms, which is a sudden disturbance of the Earth’s magnetosphere. It is well accepted that CMEs play a dominant role in causing geomagnetic storms by a direct impact, but it is still not very clear regarding their association with solar flares. The association would be helpful for forecasting geomagnetic storms directly from flares, which are much easier to observe. The Macau Science Satellite-1 (MSS-1) mission, with the scientific aim of studying the origin and evolution of the geomagnetic field, is able to accurately measure the vector geomagnetic field. Besides, it measures rapid spectral evolution of the solar X-ray irradiance of solar flares. In this study, we analyzed measurements by MSS-1 during a series of X-class flares in October of 2024, and saw the relationship between the flares and the associated geomagnetic storms. The observations support that the major geomagnetic storms tend to be associated with flares' duration in addition to flare class. We also find that long duration ones have radiated more energy in the extreme ultraviolet waveband. Being equally important, our results show that the magnetic fields measured by MSS-1, especially its external (\begin{document}$ e_1^0 $\end{document}) coefficient, can well be used for monitoring the geomagnetic disturbance.